An experimental analysis on the effect of n-pentanol- Calophyllum Inophyllum Biodiesel binary blends in CI engine characteristcis. (15th April 2019) - Ashok, B.; Jeevanantham, A.K.; Nanthagopal, K.; Saravanan, B.; Senthil Kumar, M.; Johny, Ajith; Mohan, Aravind; Kaisan, Muhammad Usman; Abubakar, Shitu
Abstract: The objective of this work is to study the addition of n -pentanol with the Calophyllum Inophyllum biodiesel to evaluate the performance, emission and combustion characteristics. Five different fuel blends are prepared by varying the n -pentanol fraction (10%, 20%, 30%, 40% and 50%) on volume basis with biodiesel. The prepared samples are tested in single cylinder constant speed CI engine. The addition of n -pentanol with biodiesel improves the thermal efficiency of the fuel blend up to 30% as compared to pure biodiesel. Among all fuel samples, B90P10 blend has shown higher brake thermal efficiency as 27% which is slightly lower than BTE of diesel fuel. The brake specific fuel consumption of biodiesel-pentanol blends are increased from 4.2% to 27.3% when compared to diesel fuel (D100). However, addition of n -pentanol more than 40% shows a negative effect in terms of performance and combustion. It is noted that biodiesel and n -pentanol blends have shown 15–43% and 33–50% reduction in hydrocarbon and carbon monoxide emissions compared to diesel. Further, the oxides of nitrogen and smoke emissions are found to be lesser for n -pentanol blends while comparing to the pure biodiesel. Among all blends, B90P10 is found to have better performance and emission characteristics. Highlights: n -pentanol is add with Calophyllum Inophyllum biodiesel at fractions of 10%–50%. Engine characteristics of higher alcohol blend with biodiesel is studied. Performance of n -pentanol fraction for 10%, 20%, 30% is superior than pure biodiesel. NOx emissions is reduced for the n -pentanol fractions with biodiesel. Ignition delay is increased for the n -pentanol blends due to low cetane number.